Analisis Putusan Hakim Terhadap Tindak Pidana Kekerasan Dalam Rumah Tangga (Studi Kasus Putusan Nomor 1189/Pid.Sus/2024/PN Mdn) - Sitompul, Kristina Pujasari; Simbolon, Nur Anisa; Sembiring, Julianti; Panjaitan, Novia; Siahaan, Parlaungan Gabriel (Lembaga Dongan Dosen, 2024)
The case of domestic violence has been tried at the Medan District Court with the issuance of decision No.1189/Pid.Sus/2024/PN MDN. Through this decision, the author intends to conduct research by legally analyzing cases of domestic violence that are in conflict with the law, for criminal acts of domestic violence where women are victims. Based on the basic problems that have been described, the author raises a study entitled